Myocardial composition and contractile function of right atrial trabeculae from type 2 diabetic and nondiabetic male patients - Liam Tianlang Zhang; Amelia Sally Power; Nicholas Kang; Marie‐Louise Ward (Physiological Reports)
Abstract Diabetes impairs myocardial function. This study investigates tissue composition and contractile function of isolated atrial tissue from type 2 diabetic patients prior to heart failure. Multicellular trabeculae were dissected from freshly obtained right atrial appendage samples from consenting patients undergoing heart surgery. Trabeculae were mounted in a stress transducer at optimal length and electrically stimulated to contract. The steady‐state force produced in response to stimulation at physiological frequencies was recorded at 37°C. Myocardial composition of trabeculae from the same patient samples was examined by immunolabeling of contractile proteins, extracellular collagens (types I and III), and fibroblasts. Relative to nondiabetic, diabetic trabeculae had increased diastolic (p = 0.01) and decreased active stress (p = 0.02), with no difference in the time course of contraction and relaxation. Immunohistological findings showed that diabetic trabeculae had reduced myofilament content (p = 0.02), whereas the relative abundance of collagens type I and type III, cardiomyocytes, and fibroblasts was comparable to nondiabetic trabeculae. However, diabetic trabeculae had a significant reduction in the collagen I/III ratio (p = 0.04) with differences in fibroblast morphology. Our study demonstrated that the contractile function at this stage of diabetic heart disease was associated with small changes in myocardial composition in the right atrium.